Investigating social support, health and gender as determinants of physical activity for 55 - 70 year old adults : a thesis presented in partial fulfillment of the requirement for the degree of Master of Arts in Health Psychology at Massey University - Beagley, Vicki Margaret (Massey University, 2008)
Our global populations have low physical activity levels, which are leading to burgeoning health issues. International literature portrays New Zealand as an active nation in comparison to other western nations, yet physical activity levels are declining world wide, as well as in New Zealand. Approximately 47% of New Zealand males and 43% of New Zealand females aged from 55 to 70 years are not active enough. This study utilized an ecologically based model to investigate gender, social support, physical and mental health, in relation to levels of physical activity. The 6,413 participants were part of a nationwide cross sectional study and the analyses conducted included bivariate, mediating and moderating relationships. All the proposed hypotheses were supported, except for the moderation hypothesis. Therefore the results of this study, which is the first in New Zealand to consider these relationships, highlights the importance of social support and health when examining physical activity participation. Further research in New Zealand is now required to identify those determinants that explain even more variance in physical activity, with a view to developing effective interventions.
Keywords: Middle-aged persons; Health and hygiene; Older people; Exercise for older people; Exercise for middle-aged persons; Exercise